PENGARUH LEVERAGE DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DENGAN TAX AVOIDANCE SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2016-2020 - Hidayah, Atika Nur; Wiryaningtyas, Dwi Perwitasari; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Tax is a very potential alternative. As one of the potential sources of state revenue, the tax sector is a very appropriate choice, apart from the relatively stable amount that is also a reflection of the active participation of the community in financing development. The purpose of this study was to determine the effect of Leverage and Institutional Ownership on Firm Value through Tax Avoidance. The sampling technique used in this research is purposive sampling. The population in this study is the Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2020. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, Leverage has a positive but not significant effect on Tax avoidance., Institutional ownership has a positive but not significant effect on Tax avoidance, Leverage has a significant positive effect on firm value, Institutional ownership has a positive but significant effect on firm value , Tax avoidance has a positive but not significant effect on firm value. The results of the indirect effect hypothesis test show that Leverage on Company Value through Tax Avoidance is positive but not significant. Institutional Ownership on Company Value through Tax Avoidance is posiyive but not significant.